Organizational Emotional Capability Perspective: Research on the Impact of Psychological Capital on Enterprise Safety Performance - Peng, Cheng; Xue, Ke; Tian, Yue; Zhang, Xuezhou; Jing, Xi; Luo, Haolun (Frontiers in Psychology, 2022)
Theoretical researchers of manager psychology have excellent potential to extend its research framework to more enterprise application areas, such as innovation, performance, and safety in production. Research in these areas has also been increasing in the past ten years. Psychological capital is composed of four aspects: self-efficacy, hope, optimism, and tenacity. It plays an essential role in stimulating organizational growth and improving organizational performance. In safety management work, managers, as the core members of the organization, have a relationship between their psychological capital and employees' safety performance. Nevertheless, the closeness of the relationship between psychological capital and employee safety performance has not been fully demonstrated by academic circles. Based on positive psychology theory, this paper conducts a questionnaire survey of 157 managers and 314 employees related to safety work in manufacturing enterprises. From the new perspective of organizational emotional capability, this paper investigates the complex and extensive social-psychological role in organizations and combs, analyzes, and integrates relevant psychological research to construct the influence mechanism of managers' psychological capital and employee safety performance. Finally, the three important issues found based on data analysis were：1. Managers' psychological capital has a significant positive impact both on employee safety performance and organizational emotional capability; 2. Organizational emotional capability has a significant positive impact on employee safety performance; 3. organizational emotional capability plays a partial mediating role in the relationship between managers' psychological capital and employee safety performance.